Improved procedures for immobilisation of oligonucleotides on gold-coated piezoelectric quartz crystals - Tombelli, S.; Mascini, Marco; Turner, Anthony P. F. (Elsevier, 2002)
The high sensitivity and specificity of DNA hybridisation techniques makes them powerful tools for environmental or clinical analysis. This work describes the development of a DNA piezoelectric biosensor for the detection of the hybridisation reaction. Attention was focused on the choice of the coating chemistry that could be used for the immobilisation of oligonucleotides onto the gold surface of the quartz crystal. Four immobilisation procedures were tested and compared considering the amount of immobilised probe, the extent of the hybridisation reaction, the possibility of regeneration and the absence of non-specific adsorption. All the experiments were performed with oligonucleotides of 25 bases (probe, target and non-complementary oligonucleotide).The four coating methods were all based on the use of self-assembled monolayers. Three of them employed the interaction between streptavidin and biotin for the immobilisation of a biotinylated probe.Results indicated that immobilisation of a biotinylated probe on streptavidin linked to a layer of carboxylated dextran provides higher sensitivity for the detection of the hybridisation reaction, absence of non-specific adsorption and a higher stability with respect to the regeneration step.